Urban transition in Hanoi : huge challenges ahead - Labbé, Danielle, 1977- (Trends in Southeast Asia, 2021)
Vietnam is in the midst of one of the world's most rapid and intensive rural-to-urban transitions. In Hanoi, heritage preservation has gained significant policy attention over the last decades, but efforts continue to focus on the Old Quarter and Colonial City to the exclusion of collective socialist housing complexes and former village areas, and natural features such as canals and urban lakes. Parks and public spaces are urgently needed to offset the high residential densities and to improve the quality of life of residents.